INFLUENCE OF TGT TYPE COOPERATIVE LEARNING MODEL ON EARTH STRUCTURE MATERIAL AND ITS DYNAMICS ON STUDENT KNOWLEDGE COMPETENCE IN SMPN 01 ULAKAN TAPAKIS - kurniawan, heru; Lestari, Tuti (Universe, 2024)
This study aims to determine the effect of the TGT type cooperative learning model on the material of the earth's structure and its dynamics on the knowledge competence of students at SMPN 01 Ulakan Tapakis. The research method used is a quantitative method. The form of this research is classroom action research. The nature of this research is collaboration with classroom action research design. The subjects of this study were seventh grade students of SMPN 01 Ulakan Tapakis. The collected data is processed and analyzed by calculating percentages and numbers. The study was conducted with a pretest and posttest in the experimental class and control class. The data obtained by the average pretest and posttest results in the experimental class was 40.19 and increased to 61.54. In the control class that is 41.35 and rose to 47.69. the similarity test of the two averages obtained is 5.22. Where the similarity test of the two averages is obtained from the N-gain value. The similarity test of two averages serves to see whether there is an increase or not in the treatment before and after. From the data above, it can be concluded that there is an effect of the treatment of the TGT type cooperative learning model on the knowledge competence of students at SMPN 01 Ulakan Tapakis.